UNIVERSALITY OF EDUCATION AND CULTURE AND EDUCATIONAL ACCESS: IN THE CONTEXT OF NATIONAL CURRICULUM FRAMEWORK 2022 - Kumar, Anil; Singh, Gopal (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Along with the emergence, development and progress of human life, there has been a change in the nature of education, culture, thoughts, behavior and activities. The culture of education has developed from ancient times to the present technological era. In ancient times, the primary education of the Gurukul system has now settled in the primary education school along with nursery, LKG, UKG. The place of family education has become very secondary. Every person has become completely dependent on school and college. While the minimum age for admission in Gurukul was eight years, now there is a well-planned scheme to get admission in Bal Vatika in two to two and a half years. The inclusion of psychology in education has been revolutionary for the modern education system. Psychologists have said that the first five years are important for the child. Technology and modern stimulating resources have proved to be very effective for him. Indian lifestyle is diverse as compared to other countries. Keeping in mind these diversities and needs of country, time and circumstances, Indian National Education Policy 2020 was introduced in the 21st century after several decades. By making structural changes in this policy, better management of primary education and pre-primary education has been done. To achieve the criteria set in the National Education Policy 2020, it has been kept in mind in the National Curriculum Framework 2022 that universal and educational access to education culture should be accessible to every boy and girl.